Representações sociais de amor romântico nas músicas mais tocadas nas rádios brasileiras em 2015 - Pontual, Marco Antonio de Deus (2017)
The aim of this study was to analyze the social representations of romantic love found in the lyrics of the songs most played in Brazilian radio in 2015. We analyzed 100 songs, which were identified using AudioMonitor, a radio monitoring software that registers and stores in real time data from more than 4.500 radio stations countrywide. The data analysis was conducted using Alceste’s Descending Hierarchical Classification associated with categoricthematic content analysis, in addition to descriptive statistics for the characterization of the Brazilian radio music in 2015. In regards to the lyics, the data was divided into two corpora, here seen as complementary stages: corpus 1, containing 95 songs which had romantic love as their central theme and corpus 2, composed of 44 songs which approached love from a limerent perspective. On the first stage, Alceste’s analysis indicated the existence of four classes organized in two main axis and two subaxis. Each one of the classes dealt with a different stage of the romantic cycle. On the first axis, relationship in course, are present the stages of the romantic relationship, Class 1 being responsible for elements associated with positive interactions and the beginning of the relationship, Class 2 refering to elements of conflict and Class 4 to elements associated with the ending of the relationship. The second axis, pre-relationship, which contains only Class 3, courtship, encompasses different behavioral elements of the individual who intends to start a romantic relationship. In a second analysis, done with Alceste using only songs classified as limerent, two classes emerged: Class 1, stabilization and euphoria, and Class 2, instability and despair. Such classes highlight the ambivalent character of the limerent situation, which alternates between states of extreme happiness and extreme sorrow. Complentary to the Descending Hierarchical Classification, the content analysis, carried through using the limerent lyrics, emphasized the stage of limerence in which each song is (beginnings, pleasant thoughts, traits and memories, intensification through hardships, despair / euphoria and stabilization) with its respective limerent traits (intrusive thoughts, distortion of reality, physiological changes, emotional changes and excessive behavior). Among the several social objects present in the lyrics of the analyzed songs, we discuss the main thematic axis of the social representations of romantic love that were found: the romantic cycle; limerent love; male/female dynamics; and love and alcohol consumption.